Hubungan Antara Kepercayaan Diri Dengan Penyesuaian Sosial Pada Siswa - Devita Andriani Putri (ILIN Institute, 2020)
The aim of the research was to determine the significance of the relationship between self-confidence and social adjustment on grade XI students in SMA Negeri 1 Tuntang. The method used in this research was correlational with a quantitative approach. There were 155 students became the subject. Questionnaire was used to collect the data. Moreover, this research used statistic correlations according to kendalls tau for the data analysis method. From the research that had been done, the results were match with the obtained value from the highest value between Confidence and Social Adjustment. Furthermore, the results of the two variables were in high order. Hypothesis test results with a correlation value of 0.06 and Sig. 0.282 ? 0.06. Therefore, itu could be concluded test from the research, the H0 hypothesis was rejected which meant there was no significant relationship between Confidence and Social Adjustment on grade XI students in SMA Negeri 1 Tuntang